Identification of L-Cysteinamide as a Potent Inhibitor of Tyrosinase-Mediated Dopachrome Formation and Eumelanin Synthesis - Hyun Kyung Lee; Jae Won Ha; Yun Jeong Hwang; Yong Chool Boo (MDPI AG, 2021)
The purpose of this study is to identify amino acid derivatives with potent anti-eumelanogenic activity. First, we compared the effects of twenty different amidated amino acids on tyrosinase (TYR)-mediated dopachrome formation in vitro and melanin content in dark-pigmented human melanoma MNT-1 cells. The results showed that only L-cysteinamide inhibited TYR-mediated dopachrome formation in vitro and reduced the melanin content of cells. Next, the antimelanogenic effect of L-cysteinamide was compared to those of other thiol compounds (L-cysteine, N-acetyl L-cysteine, glutathione, L-cysteine ethyl ester, N-acetyl L-cysteinamide, and cysteamine) and positive controls with known antimelanogenic effects (kojic acid and β-arbutin). The results showed the unique properties of L-cysteinamide, which effectively reduces melanin content without causing cytotoxicity. L-Cysteinamide did not affect the mRNA and protein levels of TYR, tyrosinase-related protein 1, and dopachrome tautomerase in MNT-1 cells. L-Cysteinamide exhibited similar properties in normal human epidermal melanocytes (HEMs). Experiments using mushroom TYR suggest that L-cysteinamide at certain concentrations can inhibit eumelanin synthesis through a dual mechanism by inhibiting TYR-catalyzed dopaquinone synthesis and by diverting the synthesized dopaquinone to the formation of DOPA-cysteinamide conjugates rather than dopachrome. Finally, L-cysteinamide was shown to increase pheomelanin content while decreasing eumelanin and total melanin contents in MNT-1 cells. This study suggests that L-cysteinamide has an optimal structure that can effectively and safely inhibit eumelanin synthesis in MNT-1 cells and HEMs, and will be useful in controlling skin hyperpigmentation.